OPTIMASI PROSES EKSTRAKSI OLEORESIN LADA HITAM SECARA MASERASI DAN BANTUAN GELOMBANG ULTRASONIK MENGGUNAKAN METODE PERMUKAAN RESPON (Optimization on Extraction Of Oleoresin From Black Pepper (Piper nigrum L.) Using Maceration And Ultrasonic Method By Resp - Fitriyana, Liya; Salamun, Adi; Syaubari, Syaubari (Jurnal Hasil Penelitian Industri, 2016)
The purpose of this study is to determine the optimum conditions of extraction usingconventional methods (maceration) and ultrasonic methods by using Response Surface Method (RSM). Thevariables used in this study are ratio of solvent to black pepper, temperature and time of extraction. Solventused in this study is 99% ethanol. The biggest yield of oleoresin using maceration method was 4.42% with aratio of solvent to black pepper for 1:4 g/mL and extraction time of 4.68 hours. The biggest yield of oleoresinusing ultrasonic method was 4.94% in the ratio of solvent to black pepper for 1:5 g/mL, temperature extraction70Â° C and extraction time 4 hours. GC-MS analysis showed that the piperine contained in oleoresin extractedby using maceration and ultrasonic methods are 69.92% and 63.5%, respectively. FT-IR analysis showed thatoleoresin extracted using maceration and ultrasonic methods have piperine bound. Organoleptic test showedthat oleoresin produced by using maceration and ultrasonic extraction method meet the requirement of SNI 06-2388-1998 (dark brown color, pepper smell and thick paste form).